No difference in the outcome of metastatic thyroid cancer patients when using recombinant or endogenous TSH. Issue 4 (October 2020) - Campopiano, Maria Cristina; Podestà, Debora; Bianchi, Francesca; Giani, Carlotta; Agate, Laura; Bottici, Valeria; Cappagli, Virginia; Lorusso, Loredana; Matrone, Antonio; Puleo, Luciana; Valerio, Laura; Viola, David; et al.
Abstract : Objective: : At present, recombinant TSH cannot be used for the treatment of metastatic differentiated thyroid cancer patients. The aim of this study was to evaluate if the type of TSH stimulation, recombinant or endogenous, had an impact on the outcome of these patients. Design and methods: : We compared the outcome of two propensity score-matched groups of metastatic patients, stimulated by either only recombinant TSH ( n = 43) or only endogenous TSH ( n = 34). Results: : As expected from the matching procedure, the clinical–pathological features and the cumulative 131-I activities administered to the two groups were very similar. After 4 years of follow-up, 4% of patients were cured, 3% had biochemical disease and 93% had structural disease. However, 91% of patients obtained a clinical benefit from this therapy in terms of stabilization of the disease or complete remission or partial response. When considering the two groups separately, we did not find any difference in their outcome. When considering the response to 131-I therapy of the single type of metastases, 8% of lymph node metastases and 8% of lung metastases disappeared but none of the bone metastases. The response to 131-I therapy of the single type of metastases was similar when we looked at the two groups separately. Conclusions: : This study shows (i) an overall clinical benefit of the 131-I therapy, since the majority of patients remained affected but with a stable disease, and (ii) that the preparation with either recombinant or endogenous TSH has no impact on the 131-I therapy efficacy and the outcome of our two groups of patients.